Pertimbangan dan Alasan Pasien Hipertensi Menjalani Terapi Alternatif Komplementer Bekam di Kabupaten Banyumas - Kamaluddin, Ridlwan (Jurnal Keperawatan Soedirman, 2010)
Current trends in treatment of hypertension was use of complementary and alternative therapy (CAT). Selection of treatment of hypertension is influenced by many factors such as culture, education, beliefs, religion and others. In Banyumas, there are several complementary and alternative therapies clinics and one of the most widely used therapies by people to treat hypertension was cupping therapy. The aim of this research will explore considerations and reasons for hypertensive patients who undergone complementary alternative therapies; cupping therapy. This study used descriptive phenomenological qualitative design of hypertensive patients who undergone cupping therapy. Data were obtained through in-depth interviews. Colaizzi method used in data analysis process. The theme of the first study was the decision-making process that includes social factors (family support, discussion with the family) and psychological (believed to someone else). The second theme was the reason for undergone cupping therapy such keep away from the side effects of drugs, affordable prices, the efficacy of therapy and religious teachings. The reason of hypertensive patients who undergone cupping therapy was very varied and unique. Researchers suggest the need for nurses as a cupping therapy practitioners and serve as one of the nursing services provided to the public.